2017
DOI: 10.1177/1391561417713129
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Direct Investment and Poverty Reduction

Abstract: It is widely proclaimed that capital account liberalization would immensely benefit developing economies because once capital controls are lifted, developing economies create a potential for movement of capital. And, this free movement of capital could possibly increase growth thereby lifting millions out of poverty. India has been gradually liberalizing since the 1980s and throughout more capital inflows were observed compared to outflows. Also, the composition of capital flows has been changing since the 198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…While Lehnert, Benmamoun, and Zhao (); Gohou and Soumare (); Dollar and Kraay (); and Klein et al () support the poverty reduction hypothesis, Kosack and Tobin () dismiss the poverty reduction hypothesis and argue that FDI lowers the rate of human development in most less‐developed economies. Similarly, Agarwal and Atri () tested an FDI poverty reduction hypothesis in India and other South Asian Association for Regional Cooperation (SAARC) countries by using both FDI inflows and outflows. They employed two poverty indicators, namely, a head count ratio and poverty gap index.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…While Lehnert, Benmamoun, and Zhao (); Gohou and Soumare (); Dollar and Kraay (); and Klein et al () support the poverty reduction hypothesis, Kosack and Tobin () dismiss the poverty reduction hypothesis and argue that FDI lowers the rate of human development in most less‐developed economies. Similarly, Agarwal and Atri () tested an FDI poverty reduction hypothesis in India and other South Asian Association for Regional Cooperation (SAARC) countries by using both FDI inflows and outflows. They employed two poverty indicators, namely, a head count ratio and poverty gap index.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is imperative to note that poverty is a multidimensional phenomenon. However, the framework in current literature is dominated by one‐dimensional or monetary measures (Agarwal & Atri, ; Alfaro, ; Almfraji, Almsafir, & Yao, ; Blomstrom, Lipsey, & Zejan, ; Borensztein, de Gregoria, & Lee, ; De Mello, ; Shamim, Azeem, & Naqvi, ; Ucal, ; Whalley & Weisbrod, ). A one‐dimensional measure of economic development does not reflect the equity attributes of the economy and may neglect the key aspects of societal welfare.…”
Section: Introductionmentioning
confidence: 99%
“…The past research that found the impact of FDI to reduce poverty significantly (see, Khan et al, 2019;Agarwal et al, 2017;Shamim et al, 2014;Jalilian and Weiss, 2002;Fowowe and Shuaibu, 2014;Zaman et al, 2012;Baradwaj, 2014;Gohou and Soumare, 2012). However, some other studies found that FDI impacted negatively on poverty alleviation are (Dhrifi et al, 2020;Ali et al, 2010;Huang et al, 2010).…”
Section: Impacts Of Linear and Nonlinear Ardlmentioning
confidence: 99%
“…It means the critical macro-economic variable of the country is not effectively implemented. Agarwal et al (2017) conducted an empirical study by comparing FDI and poverty in India between 1981 and2011. The ARDL approach shows that FDI has a negative impact on the poverty level in India.…”
Section: Empiricalmentioning
confidence: 99%
“…The choice of period and countries (see appendix 1) were dictated on the availability of data. In this study's analysis, we follow Gnangnon (2020), Agarwal et al (2017), and Perera and Lee (2013) by using headcount ratio, which is a measure of the incidence of poverty and poverty gap index, which measures the intensity of poverty. Both headcount and poverty gap indexes are measured using the international poverty line of $1.90 per day.…”
Section: Datamentioning
confidence: 99%